The Role of Big Data Processing and Artificial Intelligence in Increasing Economic Competitiveness - Arief Budi Pratomo (Journal of Artificial Intelligence and Development, 2022)
In the increasingly developing digital era, the role of Big Data Processing and Artificial Intelligence (AI) in increasing economic competitiveness is becoming increasingly important to research. This article aims to explore the contribution of Big Data and AI in increasing economic competitiveness and provide new insights into effective strategies for utilizing these technologies. The research method used is a qualitative approach, which involves in-depth interviews with stakeholders and document analysis to gain a holistic understanding of the role of Big Data and AI in the economic context. The research results show that Big Data and AI significantly increase productivity, efficiency, innovation, creativity, and economic growth. Therefore, this article concludes that adopting this technology is important in facing challenges and exploiting opportunities to increase economic competitiveness in this digital era.